2021
DOI: 10.1055/s-0040-1721876
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Needle Fasciotomy versus Collagenase Injection for Dupuytren’s Contracture: A Systematic Review of Comparative Studies

Abstract: Introduction The purpose of this study was to review and compare clinical outcomes between percutaneous needle fasciotomy (PNF) and collagenase Clostridium histolyticum (CCH) injection for the treatment of Dupuytren’s contracture. Materials and Methods A systematic review was performed including all level I-III evidence studies investigating the clinical outcomes of PNF and CCH injection in the treatment of Dupuytren’s contracture. Results Five studies (278 CCH patients, 225 PNF patients; 285 CCH fingers, 246 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
(115 reference statements)
0
5
0
Order By: Relevance
“…In this network meta-analysis, we show that CI presents an effective treatment option, however it does not yield superior short-term results compared to NF despite a higher complication profile. Although CI, rather than NF, is thought to be associated with greater functional improvement in some reports [28], in the available RCTs the differences between the treatment modalities appeared trivial when looking at TPED and contracture reduction to 0°-5° of full extension in treated joints within 30 days. Our results are in line with recent trials that have shown similar short-to medium-term functional results [14].…”
Section: Discussionmentioning
confidence: 95%
“…In this network meta-analysis, we show that CI presents an effective treatment option, however it does not yield superior short-term results compared to NF despite a higher complication profile. Although CI, rather than NF, is thought to be associated with greater functional improvement in some reports [28], in the available RCTs the differences between the treatment modalities appeared trivial when looking at TPED and contracture reduction to 0°-5° of full extension in treated joints within 30 days. Our results are in line with recent trials that have shown similar short-to medium-term functional results [14].…”
Section: Discussionmentioning
confidence: 95%
“…A previous systematic review of collagenase injection and PNF included three RCTs (also included in our review) and two retrospective cohort studies but with different assessment results ( 21 ). Judging the risk of bias is a complex procedure and requires meticulous reasoning and adequate knowledge of the subject of the study.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reviews have approached the matter ( 21 , 24 ), but to our knowledge, this is the first study that primarily investigates the methodological quality of RCTs comparing collagenase injection with PFN in the treatment of DD. Our results regarding the quality of the published studies would be helpful when proposing future practice guidelines, particularly since the results of these published RCTs may apply to the treatment of isolated MCP joint contractures but cannot be generalized to more severe DD with PIP involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Blind peer-review, sincere and intelligent reviewers, along with our editorial team put their thoughts and skillfully accepted great hallmarked articles. [1][2][3][4][5][6][7][8][9][10][11][12][13] COVID-19 struck us badly, losing our near and dear ones in early 2020. Most countries reeled toward lockdowns, disrupting normalcy.…”
mentioning
confidence: 99%
“…Blind peer-review, sincere and intelligent reviewers, along with our editorial team put their thoughts and skillfully accepted great hallmarked articles. 1 2 3 4 5 6 7 8 9 10 11 12 13…”
mentioning
confidence: 99%